Implementation of HOTS Assessment in Islamic Religion Lesson in 3rd Grade Islamic Elementary School East Java - Vivin Devi Prahesti; Siti Fatonah; Anis Maisarah (Program Studi PGMI UIN Salatiga, 2023)
Embedded critical thinkers, problem solvers, and creativities outcomes are achieved by HOTS assessment making learning display accurate. The research aims to conduct a HOTS assessment on religious learning based on the HOTS assessment in 3rd grade MI. The research analyzes assessments by teachers in class with HOTS questions to train higher thinking order students in 3rd grade. The type of research is descriptive qualitative research that examines questions based on Bloom’s taxonomy. The subject of research is teachers in MI Roudlotul Jannah. The researchers take the data through interviews and observations. The interview techniques were conducted to know how to perform the HOTS assessment to the students, while observation techniques were taught to know religion learning based on the HOTS assessment. HOTS assessment on religion learning is that Al Qur’an Hadis, Fiqih, and Akidah Akhlak are performed on some daily tests to train critical thinking, creativity, communication, and collaboration based on Bloom’s taxonomy. The researchers conclude religion learning with HOTS questions becomes a challenge for students in the learning processes, and teachers have not known HOTS questions, so that they feel hard to understand students in learning because of the diverse students’ skills. This improves students’ skill. The finding research is questions based on HOTS in learning that is implemented by analyzing Islamic religion lessons based on Bloom’s taxonomy, examining basic competencies to improve students’ ability in the way students think.